Relationship between morphometric measurements and blood parameters in horses with varying adiposity levels and physiological conditions - Arash Omidi; Aria Rasooli; Saeed Nazifi; Abbas Heydari; Mohammad Seirafinia (Veterinary Medicine and Science)
Abstract Background Understanding and finding the correlation between morphometric measurements and horse blood parameters is crucial for predicting equine metabolic issues. Objective This study aims to analyse morphometric measurements and blood samples in horses with varying adiposity levels. Study design Cross‐sectional observational. Methods A total of 50 horses were included in the study and categorized into groups based on their body condition score (BCS) and cresty neck score (CNS). Results The insulin concentration was significantly higher in overweight horses (p = 0.022). Female horses exhibited higher cortisol concentrations (p = 0.025) and girth circumference at the withers (p = 0.004) compared to males. Lactating mares exhibited higher concentrations of serum total protein (p = 0.012) and globulin (p = 0.003). A positive correlation was observed between BCS and insulin concentrations (r = 0.290, p = 0.041). Negative correlations were found between neck circumference to height at withers and glucose (r = −0.309, p = 0.029), CNS and glucose (r = −0.315, p = 0.026) as well as between crest diameter and cortisol (r = −0.360, p = 0.01). Main limitations Increasing the sample size and conducting longitudinal studies would enhance the study's validity and reliability. Conclusion Although insulin, glucose and cortisol concentrations have predictive capabilities based on signs and certain morphometric measurements, their correlations are not always strong. Therefore, this study challenges the notion that all overweight horses are unhealthy, as overweight horses can still have good metabolic health. Conversely, lean horses may also experience metabolic issues. Hence, relying solely on visual cues is insufficient to diagnose the metabolic status of horses. Other factors must also be considered to assess their health status accurately.